Leptin Stimulates Cellular Glycolysis Through a STAT3 Dependent Mechanism in Tilapia - Douros, Jonathan D.; Baltzegar, David A.; Reading, Benjamin J.; Seale, Andre P.; Lerner, Darren T.; Grau, E. Gordon; Borski, Russell J. (Frontiers in Endocrinology, 2018)
We assessed if leptin, a cytokine hormone known to enhance energy expenditure by promoting lipid and carbohydrate catabolism in response to physiologic stress, might directly regulate cellular glycolysis. A transcriptomic analysis of prolactin cells in the tilapia (Oreochromis mossambicus) pituitary rostral pars distalis (RPD) revealed that recombinant leptin (rtLep) differentially regulates 1,995 genes, in vitro. Machine learning algorithms and clustering analyses shows leptin influences numerous cellular gene networks including metabolism; protein processing transport and metabolism; cell cycle and the hypoxia response. Leptin stimulates transcript abundance of the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (gapdh) in a covariate manner to the hypoxic stress gene network. Orthogonal tests confirm that rtLep dose-dependently increases gapdh gene expression in the RPD along with transcript abundance of 6-phosphofructo-1-kinase (pfk1), the rate limiting glycolytic enzyme. Functional testing demonstrated that leptin stimulates PFK activity and glycolytic output, while Stattic (a STAT3 blocker) was sufficient to suppress these responses, indicating leptin stimulates glycolysis through a STAT3-dependent mechanism. Leptin also stimulated pfk1 gene expression and lactate production in primary hepatocyte incubations in a similar manner to those shown for the pituitary RPD. This work characterizes a critical metabolic action of leptin to directly stimulate glycolysis across tissue types in a teleost model system, and suggest that leptin may promote energy expenditure, in part, by stimulating glycolysis. These data in a teleost, suggest that one of leptin’s ancient, highly-conserved functions among vertebrates may be stimulation of glycolysis to facilitate the energetic needs associated with various stressors.